Buku pintar adat perkawinan Nusantara - Hamidin, Aep S. (Banguntapan, Jogjakarta : DIVA Press, 2012)
Marriage customs and rites in Indonesia.
Includes bibliographical references (p. 191-192).
Keywords: Marriage customs and rites -- Indonesia